Synergistic effect of antimicrobial activity between Centella asiatica and Curcuma domestica loir towards Gram-positive bacteria - Putri Shareen, Rosman; Norhazlin, Jusoh; Wan Nurul Hidayah, Wan Anuar; Saiyidah Nafisah, Hashim; Tan, Suat Hian (Malaysian Society for Microbiology, 2025)
Aims: The rising threat of antimicrobial resistance (AMR) has become one of the most critical global concerns. The resistance properties exhibited by these microorganisms cause the current antibacterial agents to become ineffective. The aim of this study was to assess the synergistic effect of ethanolic extracts of Centella asiatica and Curcuma domestica loir (CDL) leaves against Gram-positive bacteria.